Method for recycling graphite by-product
By treating graphite by-products, including inert gas, vacuuming and high-temperature insulation in the sealed container, the problem of difficult removal of magnetic impurities in the graphite by-products is solved, significantly improving its performance and enabling it to be reused.
Patent Information
- Application Number
- CN202411807708.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to efficiently remove magnetic impurities in graphite by-products in the negative electrode materials of lithium-ion batteries and improve their defects, resulting in their inability to be effectively reused.
By placing the graphite by-product in a closed container, inert gas is introduced, vacuumed, heated and heated for multiple insulation treatments, the inert gas and vacuum are repeatedly introduced, which promotes the volatility of magnetic metal impurities and improves the graphite structure.
Effectively remove magnetic impurities in graphite by-products, improve their defects, improve tap density, reduce specific surface area and first charge and discharge efficiency, significantly improve the performance of graphite by-products, and enable them to be reused.
Smart Images

Figure CN119650924A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a method for recycling graphite byproducts. Background Art
[0002] In the production process of lithium-ion batteries, the quality of negative electrode materials has a crucial impact on the performance of the final product. In order to ensure the purity of negative electrode materials and the consistency of particle size, demagnetization and screening processes are usually added to the finished product processing. However, these processes inevitably produce a certain amount of by-products, including magnetic impurities and graphite by-products such as screen material. These by-products have many inherent defects, high magnetic impurities, and large specific surface area (specific surface area>1.8m 2 / g), low initial charge and discharge efficiency (initial efficiency 80-90%), low tap density (tap density 0.75-0.95g / cm 3 ), Raman spectroscopy I D / I G Values greater than 0.12 are often considered defective or scrap.
[0003] In response to the above problems, the industry generally adopts the method of mixing graphite by-products with conventional products for reuse, but when the content of magnetic substances is too high, conventional mixing methods are difficult to meet the needs of large-scale processing. At present, the treatment methods for graphite by-products with high magnetic substance content mainly include acid washing demagnetization and high-temperature demagnetization. Although acid washing can effectively remove some impurities, it cannot improve the defects of graphite by-products, and the acid washing process may change the pH value of graphite, thereby affecting the long-term stability of the battery. On the other hand, although the high-temperature demagnetization method can effectively remove magnetic substances by heating to extreme temperatures above 2800°C, this method has extremely high energy consumption and huge economic costs, and is not suitable for large-scale industrial applications.
[0004] Therefore, there is an urgent need for a method for recycling graphite byproducts to efficiently remove magnetic impurities and improve the defects of graphite byproducts. Summary of the invention
[0005] In view of the above problems, an object of the present invention is to provide a method for recycling graphite by-products, which can efficiently remove magnetic impurities and improve the defects of graphite by-products.
[0006] To achieve the above objectives, the present invention provides a method for recycling graphite byproducts, comprising the following steps:
[0007] S1. Place the graphite byproduct into a sealed container;
[0008] S2. Introduce inert gas into the sealed container;
[0009] S3. Evacuate the sealed container;
[0010] S4, heating the sealed container and sequentially performing a first heat preservation and a second heat preservation, and repeating steps S2 to S3 during the second heat preservation process;
[0011] S5, cooling after step S4.
[0012] Compared with the prior art, the present invention places the graphite byproduct in a sealed container and introduces an inert gas to prevent oxidation reaction during the subsequent heating process; then the container is evacuated, and the low-pressure environment is used to promote the magnetic metal impurities to reach their saturated vapor pressure and volatilize more easily. Then it is heated to a specific temperature and subjected to the first heat preservation treatment. During this period, the magnetic metal obtains more energy and is easier to separate from the graphite structure and fully volatilize; in particular, the inert gas and vacuum are repeatedly introduced during the second heat preservation period to effectively bring out the vaporized metal elements to prevent them from re-condensing back on the graphite, while maintaining a lower air pressure again to promote the overflow of more metal impurities, thereby efficiently removing magnetic impurities. In addition, during the heating and heat preservation process, as the temperature rises, the atoms on the surface of the graphite obtain sufficient thermal energy and can be rearranged to form a more regular and compact structure, which can reduce the number of micropores and cracks, thereby significantly improving the defects of the graphite byproducts; finally, the improved graphite structure is fixed after cooling treatment to ensure the stability of the performance of the graphite material. Therefore, the preparation method of the present invention can effectively remove magnetic impurities and improve the defects of graphite by-products, so that the graphite by-products that could only be treated as waste can be reused.
[0013] As an embodiment, the magnetic substance content of the graphite byproduct in step S1 is greater than 80 ppm and the specific surface area is greater than 1.8 m 2 / g, Raman I D / I G Greater than 0.12, tap density 0.75~0.95g / cm 3 , the initial effect is 80-90%.
[0014] As an implementation scheme, the sealed container in step S1 is any one of a tubular furnace, a box furnace, an Acheson graphitization furnace, an inner string graphitization furnace, a vacuum graphitization furnace, and a continuous graphitization furnace.
[0015] As an embodiment, the time for passing the inert gas in step S2 is 10 to 120 minutes. For example, the time for passing the inert gas can be, but is not limited to, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, and 120 minutes.
[0016] As an embodiment, the inert gas in step S2 is nitrogen or argon.
[0017] As an embodiment, step S3 includes stopping the introduction of the inert gas and then evacuating the sealed container to a pressure of -0.03 MPa to -0.08 MPa. The pressure may be, but is not limited to, -0.03 MPa, -0.04 MPa, -0.05 MPa, -0.07 MPa, and -0.08 MPa.
[0018] As an embodiment, step S4 includes heating the sealed container to 1600°C to 2400°C, and the first insulation time is 30min to 960min. Preferably, the sealed container is heated to 1900°C to 2400°C. As an example, the sealed container is heated to 1600°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. Specifically, the first insulation time may be, but is not limited to, 30min, 60min, 90min, 120min, 150min, 200min, 300min, 400min, 500min, 600min, 660min, 760min, 850min, 900min. The temperature range of 1600°C to 2400°C is selected to adjust the vapor pressure of the metal element, and the difference in vapor pressure between graphite and the metal element at the same temperature is used to evaporate the metal element, thereby reducing magnetic impurities. Within this temperature range, the defects of the graphite by-product can be further improved, and the graphite surface can be rearranged, thereby improving the specific surface, first effect and vibration compaction of the graphite by-product. That is, the preparation method of the present invention can efficiently remove magnetic impurities and improve the defects of graphite by-products at a relatively low temperature.
[0019] As an embodiment, the second insulation time is 30min to 960min. Specifically, the second insulation time may be, but is not limited to, 30min, 60min, 90min, 120min, 150min, 200min, 300min, 400min, 500min, 600min, 660min, 760min, 850min, 900min. Specifically, the temperature of the second insulation is the same as the temperature of the first insulation.
[0020] As an embodiment, the cooling is natural cooling. Natural cooling provides a gentler cooling rate, which helps to maintain the microstructural integrity of the graphite byproduct and ensures that its physical and chemical properties are stable.
[0021] As an implementation scheme, step S4 includes repeating steps S2 to S3 once. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the corresponding relationship diagram between the saturated vapor pressure and temperature of different metal elements.
[0023] Figure 2 Graphs showing the tap density of the graphite byproducts obtained in Examples 1 to 5.
[0024] Figure 3 This is a graph showing the specific surface area of the graphite byproducts obtained in Examples 1 to 5.
[0025] Figure 4 This is a graph of the first charge efficiency of the graphite byproducts obtained in Examples 1 to 5.
[0026] Figure 5 Graph showing the magnetic substance content of the graphite byproducts obtained in Examples 1 to 5.
[0027] Figure 6 1 is a Raman spectrum of the graphite byproduct obtained in Examples 1 to 5. DETAILED DESCRIPTION
[0028] Figure 1 The relationship between the saturated vapor pressure and temperature of different metal elements (iron Fe, nickel Ni, chromium Cr, zinc Zn) and carbon C at high temperatures is shown. It can be observed that when the temperature exceeds 2000°C, the vapor pressure of iron (Fe), nickel (Ni), chromium (Cr) and zinc (Zn) exceeds 1 torr, which is about 133 Pascals (Pa), which means that these metals will evaporate in large quantities at this temperature. In contrast, the vapor pressure of carbon (C) at the same temperature is only 0.01 Pascals (Pa), which indicates that it hardly evaporates. This comparison shows that the volatility of different elements at extremely high temperatures is significantly different. Based on this characteristic, the present application proposes a method for recycling graphite by-products, which includes S1, placing the graphite by-products into a closed container; S2, introducing an inert gas into the closed container; S3, evacuating the closed container; S4, heating the closed container and performing a first insulation and a second insulation in sequence, and repeating steps S2 to S3 during the second insulation process; S5, cooling after step S4; the method of the present application utilizes the difference in evaporation behavior between metal elements and carbon at high temperatures, ensuring efficient evaporation of metals while carbon remains stable, thereby allowing magnetic metals (such as iron, nickel and chromium, etc.) to be effectively separated from graphite materials.
[0029] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with examples and comparative examples. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0030] The magnetic substance content of the graphite byproduct in step (1) of Examples 1 to 5 was 85 ppm and the specific surface area was 2.2 m2 / g, Raman I D / I G The tap density is 0.15 and the tap density is 0.85g / cm 3 , the initial effect is 87%.
[0031] Example 1
[0032] This embodiment provides a method for recycling graphite byproducts, the steps comprising:
[0033] S1. Put the graphite byproduct into a box furnace;
[0034] S2. Introduce nitrogen into the box furnace for 30 minutes;
[0035] S3. Evacuate the box-type furnace to a pressure of -0.06MPa;
[0036] S4, heating the box furnace to 1600° C. and sequentially performing a first heat preservation for 60 min and a second heat preservation for 90 min, wherein steps S2 to S3 are repeated once during the second heat preservation process;
[0037] S5, performing natural cooling after step S4.
[0038] Example 2
[0039] This embodiment provides a method for recycling graphite byproducts, the steps comprising:
[0040] S1. Put the graphite byproduct into a box furnace;
[0041] S2. Introduce nitrogen into the box furnace for 30 minutes;
[0042] S3. Evacuate the box-type furnace to a pressure of -0.06MPa;
[0043] S4, heating the box furnace to 1750° C. and sequentially performing a first insulation for 60 min and a second insulation for 90 min, wherein steps S2 to S3 are repeated once during the second insulation process;
[0044] S5, performing natural cooling after step S4.
[0045] Example 3
[0046] This embodiment provides a method for recycling graphite byproducts, the steps comprising:
[0047] S1. Put the graphite byproduct into a box furnace;
[0048] S2. Introduce nitrogen into the box furnace for 30 minutes;
[0049] S3. Evacuate the box-type furnace to a pressure of -0.06MPa;
[0050] S4, heating the box furnace to 1900° C. and sequentially performing a first heat preservation for 60 min and a second heat preservation for 90 min, wherein steps S2 to S3 are repeated once during the second heat preservation process;
[0051] S5, performing natural cooling after step S4.
[0052] Example 4
[0053] This embodiment provides a method for recycling graphite byproducts, the steps comprising:
[0054] S1. Put the graphite byproduct into a box furnace;
[0055] S2. Introduce nitrogen into the box furnace for 30 minutes;
[0056] S3. Evacuate the box-type furnace to a pressure of -0.06MPa;
[0057] S4, heating the box furnace to 2050° C. and sequentially performing a first heat preservation for 60 min and a second heat preservation for 90 min, wherein steps S2 to S3 are repeated once during the second heat preservation process;
[0058] S5, performing natural cooling after step S4.
[0059] Example 5
[0060] This embodiment provides a method for recycling graphite byproducts, the steps comprising:
[0061] S1. Put the graphite byproduct into a box furnace;
[0062] S2. Introduce nitrogen into the box furnace for 30 minutes;
[0063] S3. Evacuate the box-type furnace to a pressure of -0.06MPa;
[0064] S4, heating the box furnace to 2200° C. and sequentially performing a first heat preservation for 60 min and a second heat preservation for 90 min, wherein steps S2 to S3 are repeated once during the second heat preservation process;
[0065] S5, performing natural cooling after step S4.
[0066] The graphite byproducts obtained in Examples 1 to 5 were tested for tap density using Dandong Baite. The results are as follows: Figure 2 shown.
[0067] The specific surface area of the graphite byproducts obtained in Examples 1 to 5 was tested using a surface area meter NOVA2000e. The results are as follows: Figure 3 shown.
[0068] The first efficiency of the graphite byproducts obtained in Examples 1 to 5 was tested using a half-cell test method. The results are as follows: Figure 4 As shown. The half-cell test method is: the graphite byproduct is mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 90:5:5, and coated on copper foil. The coated electrode is placed in a vacuum drying oven at a temperature of 110°C for vacuum drying for 4 hours for standby use, and then a small disc with a diameter of 14 cm is punched. Then it is transferred to a German Mikaelona glove box filled with argon gas to assemble into a 2430 button cell, with a three-component mixed solvent of 1 mol / L LiPF6 in a mixture of EC:DMC:EMC=1:1:1 (volume ratio) as the electrolyte, a metal lithium sheet as the counter electrode, and a 16μm thick Ube diaphragm as the isolation membrane to form a half-cell. The electrochemical performance of the assembled half-cell was tested on the American Arbin electrochemical detection system, with a charge and discharge voltage range of 0.005V to 2.0V, a rate of 0.1C, and the first charge efficiency was recorded.
[0069] The magnetic content of the graphite byproducts obtained in Examples 1 to 5 was tested using GB / T 24533-2009 Graphite Anode Materials for Lithium Ion Batteries. Specifically, the graphite byproducts were first dissolved in aqua regia to obtain a solution, and the solution was transferred to a volumetric flask to a fixed volume. The contents of iron (Fe), nickel (Ni), chromium, and zinc in the solution were respectively detected by ICP. Finally, the results of the four element contents were added to obtain the content of magnetic substances in the graphite byproducts. The results were measured in ppm. The results are as follows: Figure 5 shown.
[0070] The Raman spectra of the graphite byproducts obtained in Examples 1 to 5 were tested using a Raman spectrometer. The results are as follows: Figure 6 shown.
[0071] Please refer to Figure 2 The tap density of the graphite byproduct raw material and the graphite byproducts of Examples 1 to 5 is 0.85 g / cm 3 , 0.87g / cm 3 、0.92g / cm 3 , 1.03g / cm 3 , 1.02g / cm 3 , 1.03g / cm 3 That is, the tap density of the graphite byproducts of Example 1, Example 2, and Example 3 increases successively. More specifically, the tap density of the graphite byproduct of Example 3 increases by 0.18 g / cm 3This may be because high temperature promotes the rearrangement or sintering between particles, making the material structure more compact, which shows that the preparation method of the present application can effectively improve the tap density of the graphite byproduct. At the same time, the tap density values of the graphite byproducts of Examples 3 to 5 are very close and fluctuate very little, which shows that the optimal tap density can be obtained by heating the box furnace in step 4 of the present method to a temperature range of 1900 to 2400°C under vacuum conditions.
[0072] Please refer to Figure 3 The specific surface areas of the graphite byproduct raw material and the graphite byproducts of Examples 1 to 5 are 2.2 m 2 / g, 2.08m 2 / g, 1.95m 2 / g, 1.57m 2 / g, 1.55m 2 / g, 1.59m 2 / g, that is, the specific surface area of the graphite byproducts of Example 1, Example 2, and Example 3 decreases in sequence. More specifically, the specific surface area of the graphite byproduct of Example 3 decreases by 0.63 m 2 / g; This may be because high temperature can reduce the pores on the surface and inside of the graphite material, thereby reducing its specific surface area, which shows that the preparation method of the present application can effectively reduce the specific surface area of the graphite by-product. At the same time, the specific surface area values of the graphite by-products of Examples 3 to 5 are very close and fluctuate very little, which shows that the optimal specific surface area can be obtained by heating the box furnace in step 4 of the present method to a range of 1900 to 2400°C under vacuum conditions.
[0073] Please refer to Figure 4 , the first effects of the graphite by-product raw material and the graphite by-products of Examples 1 to 5 are 87%, 88%, 90.2%, 92.5%, 92.5%, and 92.4%, respectively, that is, the first effects of the graphite by-products of Examples 1, 2, and 3 are improved successively, and more specifically, the first effect of the graphite by-product of Example 3 is improved by 5.5%; this may be because high temperature can promote the reduction of graphite end faces and internal defects, so that the first charge and discharge efficiency is improved, which shows that the preparation method of the present application can effectively improve the first effect of graphite by-products. At the same time, the first effect values of the graphite by-products of Examples 3 to 5 are very close and fluctuate very little, which shows that the best first effect can be obtained by heating the box furnace in step 4 of the method to a range of 1900 to 2400°C under vacuum conditions.
[0074] Please refer to Figure 5The magnetic substance contents of the graphite by-product raw materials and the graphite by-products of Examples 1 to 3 decrease successively. More specifically, the magnetic substance contents of the graphite by-products of Examples 3 to 5 are all less than 0.1 ppm. This indicates that when the temperature rises to about 1900°C, magnetic metal elements such as Fe (iron) and Ni (nickel) will escape in large quantities due to their higher vapor pressures, causing the magnetic substance content in the material to decrease rapidly, that is, the preparation method of the present application can efficiently remove magnetic impurities.
[0075] Please refer to Figure 6 , graphite byproduct raw material, graphite byproduct of Example 1 to Example 5 D / I G are 0.15, 0.13, 0.12, 0.09, 0.09, and 0.08, respectively; that is, the peak intensity ratio of the D peak to the G peak of the graphite by-products of Example 1, Example 2, and Example 3 is continuously reduced, which further proves the reduction of defects; at the same time, the peak intensity ratio of the D peak to the G peak of the graphite by-products of Example 3 to Example 5 is very close and fluctuates very little, which indicates that when the box furnace in step 4 of the method is heated to a range of 1900 to 2400° C. under vacuum conditions, carbon atoms are rearranged, and the defects of the graphite by-products are further reduced, so that the optimal I D / I G value.
[0076] In summary, the preparation method of the present invention can process graphite byproducts with high magnetic material content and many defects, thereby significantly improving multiple key performance indicators of graphite byproducts. Specifically, the method can purify graphite byproducts with an initial magnetic impurity content of more than 80ppm to a magnetic impurity content of less than 0.1ppm, greatly improving the purity of graphite byproducts. At the same time, the tap density of graphite byproducts can be significantly improved by optimizing the graphite structure; and by improving the defects of graphite byproducts, the specific surface area, the first effect and the Raman I D / I G The graphite byproduct that would otherwise have been treated as waste can be reused.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for recycling graphite byproducts, characterized in that the steps include: S1. Place the graphite byproduct into a sealed container; S2, introducing an inert gas into the sealed container; S3, evacuating the sealed container; S4, heating the sealed container and sequentially performing a first heat preservation step and a second heat preservation step, and repeating steps S2 to S3 during the second heat preservation step; S5, cooling after step S4.
2. The method for recycling graphite byproducts according to claim 1, characterized in that: The magnetic substance content of the graphite byproduct in step S1 is greater than 80 ppm and the specific surface area is greater than 1.8 m 2 / g, Raman I D / I G Greater than 0.12, tap density 0.75~0.95g / cm 3 , the initial effect is 80-90%.
3. The method for recycling graphite byproducts according to claim 1, characterized in that: The sealed container in step S1 is any one of a tubular furnace, a box furnace, an Acheson graphitization furnace, an inner-string graphitization furnace, a vacuum graphitization furnace, and a continuous graphitization furnace.
4. The method for recycling graphite byproducts according to claim 1, characterized in that: The time for introducing the inert gas in step S2 is 10 to 120 minutes.
5. The method for recycling graphite byproducts according to claim 1, characterized in that: The inert gas in step S2 is nitrogen or argon.
6. The method for recycling graphite byproducts according to claim 1, characterized in that: Step S3 includes evacuating the sealed container to a pressure of -0.03MPa to -0.08MPa.
7. The method for recycling graphite byproducts according to claim 1, characterized in that: Step S4 includes heating the sealed container to 1600° C. to 2400° C., and the first insulation time is 30 min to 960 min.
8. The method for recycling graphite byproducts according to claim 1, characterized in that: The second insulation time is 30 min to 960 min.
9. The method for recycling graphite byproducts according to claim 1, characterized in that: The cooling is natural cooling.
10. The method for recycling graphite byproducts according to claim 1, characterized in that: Step S4 includes repeating steps S2 to S3 once.